2021
DOI: 10.1021/acsphotonics.1c00189
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Nonlocal Metasurfaces for Fully Solid-State Ultrathin Optical Systems

Abstract: Most optical systems involve a combination of lenses separated by free-space regions where light acquires the required angle-dependent phase delay for a certain functionality. Very recently, flat-optics structures have been proposed to compress these large free-space volumes and miniaturize the overall optical system. However, these early designs can only replace freespace volumes of limited length, or operate in a very narrow angular range, or require a high-index background. These issues raise questions abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 28 publications
(44 reference statements)
4
61
0
Order By: Relevance
“…[17], where the authors observed a distinct tradeoff between compression ratio and NA in monochromatic multi-layered spaceplates designed using inverse design techniques, confirming earlier theoretical predictions by Chen and Monticone in Ref. [18]. Within this context, in this paper we first elucidate the basic physical mechanisms at the origin of generic space-compression effects, and we then derive physical bounds and tradeoffs on the performance of spaceplates, with a particular focus on the issue of bandwidth, which has not yet been addressed in the literature despite its relevance for some of the main potential applications of spaceplates, particularly for imaging systems.…”
supporting
confidence: 83%
See 4 more Smart Citations
“…[17], where the authors observed a distinct tradeoff between compression ratio and NA in monochromatic multi-layered spaceplates designed using inverse design techniques, confirming earlier theoretical predictions by Chen and Monticone in Ref. [18]. Within this context, in this paper we first elucidate the basic physical mechanisms at the origin of generic space-compression effects, and we then derive physical bounds and tradeoffs on the performance of spaceplates, with a particular focus on the issue of bandwidth, which has not yet been addressed in the literature despite its relevance for some of the main potential applications of spaceplates, particularly for imaging systems.…”
supporting
confidence: 83%
“…In addition, we note that, even at a single frequency, these resonator-based designs are constrained by other fundamental tradeoffs between the numerical aperture and the length of compressed space, as demonstrated in Ref. [18].…”
mentioning
confidence: 96%
See 3 more Smart Citations